2022
DOI: 10.3389/fphar.2022.863280
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Triple Combination Cystic Fibrosis Transmembrane Conductance Regulator Modulators in Patients With Cystic Fibrosis: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Cystic fibrosis is a rare, recessive, progressive genetic disease caused by dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) protein. Small molecules have recently been developed to treat the molecular consequences of CFTR mutations and restore CFTR protein function. However, the data on triple combination therapy (mainly from Vertex Pharmaceuticals, which is most tested in clinical trials) are limited. This meta-analysis was aimed to assess the efficacy and safety of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Uma revisão sistemática anterior sobre a terapia tripla para pacientes com FC, também incluindo 6 estudos, encontrou resultados semelhantes. (24) No entanto, 1 dos estudos incluídos utilizou uma combinação diferente de moduladores (VX-659 em vez de elexacaftor, combinado com ivacaftor e tezacaftor), (25) Barry PJ et al (23) Heijerman HGM et al (14) Keating D et al (12) Keating D et al (12) Mall MA et al (16) Middleton PG et al (13) Sutharsan S et al (15) Total (95% CI) Heterogeneity: Tau 2 = 39.01, Chi 2 = 53.61, df = 6 (P < 0.00001); I 2 = 89% Test for overall effect: Z = 5.91 (P < 0.00001) -20 -10 0 10 20 Barry PJ et al (23) Heijerman HGM et al (14) Keating D et al (12) Keating D et al (12) Mall MA et al (16) Middleton PG et al (13) Sutharsan S et al (15) Total (95% CI) Heterogeneity: Tau 2 = 22.15, Chi 2 = 164.22, df = 6 (P < 0.00001); I 2 = 96% Test for overall effect: Z = 5.72 (P < 0.00001) -20 -10 0 10 20 Middleton PG et al (13) Sutharsan S et al (15) Total (95% CI) Heterogeneity: Chi 2 = 1.46, df = 1 (P = 0.23); I 2 = 32% Test for overall effect: Z = 11.91 (P < 0.00001) -20 -10 0 10 20 estudo de Mall et al, (16) publicado em 2022 e incluído em nosso estudo. A semelhança dos achados reforça a robustez dos dados que apoiam a efetividade clínica da terapia ETI.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Uma revisão sistemática anterior sobre a terapia tripla para pacientes com FC, também incluindo 6 estudos, encontrou resultados semelhantes. (24) No entanto, 1 dos estudos incluídos utilizou uma combinação diferente de moduladores (VX-659 em vez de elexacaftor, combinado com ivacaftor e tezacaftor), (25) Barry PJ et al (23) Heijerman HGM et al (14) Keating D et al (12) Keating D et al (12) Mall MA et al (16) Middleton PG et al (13) Sutharsan S et al (15) Total (95% CI) Heterogeneity: Tau 2 = 39.01, Chi 2 = 53.61, df = 6 (P < 0.00001); I 2 = 89% Test for overall effect: Z = 5.91 (P < 0.00001) -20 -10 0 10 20 Barry PJ et al (23) Heijerman HGM et al (14) Keating D et al (12) Keating D et al (12) Mall MA et al (16) Middleton PG et al (13) Sutharsan S et al (15) Total (95% CI) Heterogeneity: Tau 2 = 22.15, Chi 2 = 164.22, df = 6 (P < 0.00001); I 2 = 96% Test for overall effect: Z = 5.72 (P < 0.00001) -20 -10 0 10 20 Middleton PG et al (13) Sutharsan S et al (15) Total (95% CI) Heterogeneity: Chi 2 = 1.46, df = 1 (P = 0.23); I 2 = 32% Test for overall effect: Z = 11.91 (P < 0.00001) -20 -10 0 10 20 estudo de Mall et al, (16) publicado em 2022 e incluído em nosso estudo. A semelhança dos achados reforça a robustez dos dados que apoiam a efetividade clínica da terapia ETI.…”
Section: Discussionunclassified
“…A previous systematic review, also including 6 studies, about the triple therapy for CF patients found similar results. 24 However, 1 of the studies included used a different combination of modulators (VX-659 instead of elexacaftor, combined with ivacaftor and tezacaftor), 25 and because the search was limited to December of 2021, it did not include the study by Mall et al, 16 published in 2022 and included in our study. The similarity of the findings reinforces the robustness of data supporting the clinical effectiveness of ETI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hasta la fecha no hay recomendaciones respecto a la duración de la triterapia, pero probablemente no debiera ser un periodo inferior a 6 meses como lo han demostrado los estudios de eficacia y seguridad en niños y adultos 23 . Conocemos sólo un estudio realizado en adultos mayores de 20 años homocigotos para la mutación ∆F508 de la FQ que recientemente ha completado un seguimiento anual con buen perfil de eficacia y seguridad 24 .…”
Section: Discussionunclassified
“…Several limitations to the scope of the present study in a small number of CF participants should be mentioned. Most CF patients are now on revolutionary CFTR potentiator and/or corrector therapies and these are likely to exert impacts on vitamin E pharmacokinetic via potential effects on bile and pancreatic secretions, enterocyte functions and modulations of the intensity of RT inflammatory processes [78][79][80][81][82][83][84][85]. No attempts were made in the present study to relate plasma tocopherol kinetics to either parameters of RT or systemic inflammation/oxidative stress or to acute or chronic CF exacerbations.…”
Section: Limitationsmentioning
confidence: 96%